KINO SAN’ATI RIVOJIDA RASSOMNING O‘RNI - Salim Madartov (Social science and innovation, 2023)
In this article, the role of the cinematographer in the creation of a film is analyzed on the example of the created films. Also, the shortcomings in this direction are analyzed separately